Le decisioni pubbliche ai tempi del Coronavirus: la tutela dei diritti tra fondatezza scientifica, trasparenza e principio di precauzione (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The recent CoViD-19 emergency has made particularly evident not only the importance of the relationship between science and law for the protection of fundamental rights, but also its complexity. This paper analyses the impact that different kinds of relationships between public decision-makers and the scientific community may have on the protection of the rights involved, the main problems occurred during the CoViD-19 emergency and some possible solutions.
Keywords: CoViD-19; pandemic emergency; law and science; scientific uncertainty; precautionary principle